IMPLEMENTASI MANAJEMEN KEUANGAN TERHADAP PENGELOLAAN DANA DI SMP LABSCHOOL UNESA 3 SURABAYA - Ananda Ditasari; Wahyu Puteri Pratama; Kharisma Nur Farahana; Gizza Mardiana Nur Avisa; Nur Azlinatul Zulfa; Riqa Dwinur Aisyah; Ima Widiyanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study describes the implementation of financial management at SMP Labschool UNESA 3 Surabaya using George R. Terry’s POAC framework (Planning, Organizing, Actuating, and Controlling). Utilizing a qualitative descriptive approach, data was gathered through observations, interviews, and documentation with the school treasurer and relevant stakeholders. The findings reveal that Planning is executed transparently and participatively through the collaborative drafting of the School Activity and Budget Plan (RKAS) by principals, teachers, and committees. In the Organizing stage, roles are clearly segregated, appointing the principal as the primary supervisor and the treasurer as the technical executor. Actuating leverages digital systems like ARKAS and SIPLah for efficient fund disbursement, despite occasional government delays. Finally, Controlling involves regular budget evaluations and comprehensive monthly accountability reports (LPJ) to guide future financial Planning. Ultimately, the study concludes that the POAC-based financial management at SMP Labschool UNESA 3 Surabaya operates optimally